Pengaruh Financial Distress, Komite Audit, dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan - Kusuma, Alifta Wulan; Putry, Mellafya Cyndya; Hidayah, Tri Noor; Noviana, Fatma Ade (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Presenting financial reports with integrity will increase public trust in the company while also minimizing manipulation of financial data by management. This research aims to examine the influence of financial distress, audit committee and company size on the integrity of financial reports in cigarette companies listed on the Indonesia Stock Exchange from 2019-2023. Sample selection was based on a purposive sampling technique with the results of 4 companies as research samples. For data analysis purposes, secondary data is used in the form of company annual reports. The analysis technique uses descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, partial test and simultaneous test. Statistical results from data testing show that financial distress, audit committee and company size have no effect on the integrity of financial reports.